Competition of coagulation sink and source rate: New particle formation in the Pearl River Delta of China - Gong, Y. G.; Hu, M.; Cheng, Y. F.; H. Su; Yue, D. L.; F. Liu; Wiedensohler, A.; Wang, Z. B.; Kalesse, H.; S. Liu; ZJ Wu; Xiao, K. T.; et al. (Atmospheric Environment, 2010)
The coagulation sink and its role in new particle formation are investigated based on data obtained during the PRIDE-PRD2004 campaign at Xinken of Pearl River Delta, China. Analysis of size distributions and mode contributions of the coagulation sink show that the observed higher load of accumulation mode particles impose a significant effect on the coagulation sink and result in higher coagulation sinks at Xinken despite of the lower total particle number compared with other areas. Hence it is concluded that the higher coagulation sink may depress the occurrence frequency of new particle formation events. The strategies targeting at controlling accumulation mode particles may have influences on the frequency of new particle formation events at this area. The factors affecting the coagulation sink are evaluated. The relatively lower ambient relative humidities may weaken the coagulation sink and facilitate the occurrence of new particle formation events during noontime, while the surmise of nucleation and growth involving organic matter may imply an actually higher coagulation sink than expected. These factors have a significant influence on the ultimate fate of the newly formed nuclei and new particle formation. A comparison of event and non-event days indicates that the coagulation sink is not the only decisive factor affecting new particle formation, other factors including the precursor vapors and photochemical activity are none the less important either. Competition of coagulation sink and high source rate leads to the occurrence of new particle formation events at Xinken. Crown Copyright (C) 2010 Published by Elsevier Ltd. All rights reserved.
Keywords: aerosol-particles; atmospheric nucleation; boundary-layer; ccn; Coagulation sink; concentration; Environmental Sciences & Ecology; growth; Meteorology & Atmospheric Sciences; new particle formation; nucleation mode particles; Particle number; pride-prd2004; relative-humidity; size distribution; vapor; xinken